Management of uraemic pericarditis. Issue 5996 (6th December 1975) - Kramer, P; Wigger, W; Scheler, F
Abstract : Of 250 patients undergoing haemodialysis from 1967 to 1974 17 presented with uraemic pericarditis. Seven of these patients who had been transferred early enough to peritoneal dialysis treatment were cured without pericardiectomy (mean survival 18 months (range 6-36); no deaths). Only one patient was cured from his pericarditis by "aggressive haemodialysis." In seven out of 10 patients treated with haemodialysis, pericardiectomy finally had to be performed because of pericardial tamponade (postoperative survival 20 months (range 8-36); one death). Two patients died from pericardial tamponade before surgery. In patients with evidence of uraemic pericarditis frequent peritoneal dialysis with high fluid withdrawal is the treatment of choice, but in cardiac tamponade pericardiectomy should follow a preoperative pericardiocentesis with limited fluid aspiration. Of possible significance in the aetiology of pericarditis were the findings that 10 of the 17 patients had hypertension with cardiac enlargement and that 14 presented with evidence of underdialysis, possibly due to the reuse of dialysis components.